Management and Consideration of Anesthesia Procedures in Eclampsia: A Case Report - Rauwelio, Alvin; I Wayan Widana (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Eclampsia is a serious pregnancy complication with high maternal and fetal mortality rates. The choice of anesthetic technique in eclamptic patients must consider various factors, including the condition of the mother and fetus, the risk of complications, and the experience of the anesthesia team. Case presentation: We report the case of a 21-year-old 39-week-old primigravida (G1P0A0) with severe eclampsia who experienced two tonic-clonic seizures. The patient was intubated in the emergency room and underwent an emergency caesarean section under general anesthesia. The patient was treated in the ICU for one day and extubated on the second day. Conclusion: The choice of anesthetic technique in eclamptic patients must be done individually by considering various factors. The anesthesia team must be experienced in treating eclamptic patients and have the readiness to deal with complications that may occur.